Neurologist knowledge about interactions between antiepileptic drugs and contraceptive methods. Issue 3 (September 2016) - Suto, Hilda S.; Braga, Giordana C.; Scarpellini, Giuliano R.; Takeuchi, Leandro I.; Martins, Ana P.; Leite, João P.; Vieira, Carolina S.
Abstract: Objective: To evaluate neurologists' knowledge of contraceptive counseling for women receiving antiepileptic drugs (AEDs). Methods: An interview-based survey was conducted from February 2 to June 30, 2015, among neurologists working in Ribeirão Preto, Brazil. Direct interviews were conducted using a questionnaire that assessed knowledge of the pharmacological interactions between various contraceptive methods and six AEDs (carbamazepine, phenobarbital, topiramate, phenytoin, lamotrigine, and valproate) on the basis of WHO medical eligibility criteria for contraceptive use. Results: Among 42 neurologists who participated, 32 (76%) stated that they treated women with epilepsy and provided them with counseling for family planning. Overall, 34 (81%) recommended the use of a copper intrauterine device irrespective of the AED used, and 26 (60%) stated that they co-prescribed AEDs and hormonal contraceptives. Although 39 (93%) neurologists had knowledge that AEDs might contraindicate the use of some contraceptives, their knowledge regarding the specific drug interactions was lacking. Furthermore, 34 (81%) had no knowledge of WHO medical eligibility criteria for contraceptive use. Conclusion: Although most neurologists interviewed had knowledge of interactions between AEDs and hormonal contraceptives, they did not know which specific AEDs interacted with these agents.